Educação Alimentar e Nutricional no Ensino de História: uma abordagem transformadora para os Anos Iniciais do Fundamental em diálogo com os ODS - Galesi-Pacheco, Lilian Fernanda [UNESP]; Neto, Humberto Perinelli [UNESP]; Cervato-Mancuso, Ana Maria (Revista Ibero-Americana de Estudos em Educacao, 2025)
The aim of this work was to analyze the National Common Curricular Base and develop an educational proposal based on the articulation between History Teaching skills in the Early Years of Primary School, Food and Nutrition Education (FNE) skills and the Sustainable Development Goals (SDG), geared towards tackling contemporary global issues. The research is qualitative, applied, exploratory and descriptive. Documentary analysis was carried out on documents highlighted in Basic Education, Nutrition and the SDGs. A total of 65 skills and 35 possibilities for practical activities for FNE were constructed, linked to the History Teaching skills, associated with 13 SDGs and grouped according to the FNE Framework for Public Policies. The proposal allows FNE to be dealt with at school according to knowledge linked to the pedagogy of autonomy, which implies thinking about education based on ethics, dialog and criticality.